Factors Influencing Satisfaction and Loyalty Among Hospital Patients Towards Sustainable Health and Wellbeing - Fernando Trinidad; Eunice Mareth Querol Areola, PhD HSG; Josefina Cano, MD; Samuel PD Anantadjaya (Journal of Sustainable Community Development (JSCD), 2026)
The lack of coherent and comprehensive framework that guides establishing practical measures of healthcare service quality in hospitals through the case of level 3 hospitals outlines this study. Using the theoretical underpinnings of integrative models for healthcare quality (Service quality, Patient satisfaction, Patient loyalty, and Hospital image) combined with the SERVQUAL model (Tangibles, Reliability, Responsiveness, Assurance, Empathy,) the objective of the research is to quantify and examine patient satisfaction, patient loyalty, and hospital image, between the groups of respondents, outpatient and inpatient, as well as hospital personnel of healthcare professionals and hospital management. The study employed a mixed method case study research design on data collected through a questionnaire, and validated through interviews. Statistical tools included Mean, Standard Deviation, Pearson R, T-Test and Partial Least Squares Structural Equation Modeling (PLS-SEM). Statistical analysis revealed significant positive correlations, with all null hypotheses (H01–H06) rejected based on low p-values (< 0.05). Additionally, significant differences were observed between patients, hospital workers, management, and healthcare professionals (H07). The study's major contribution to knowledge and literature is a proposal for a policy addressing quality assurance of services for identified areas in the participating hospitals so as to achieve a sustained health and wellbeing for an identified country case.